Microplásticos em ambientes marinhos brasileiros: um estudo em praias de São Francisco do Sul - SC - Escrobot, Marcia (2023)
The main sources of microplastics entering the marine environment occur through the emission of plastic polymer waste in domestic environments, ports, ships, industries, fishing activities, as well as the incorrect disposal of these materials on beaches. It is estimated that approximately 25% are in the form of particles smaller than 5 mm, called microplastics, which have been observed in the oceans and coastal environments, putting the health of living beings at risk, affecting directly or indirectly. The objective of this dissertation was to analyze the occurrence of microplastics, investigate the chemical nature of the polymers that make up this material in the coastal region of São Francisco do Sul (SC) and verify existing studies on the subject within the scope of national research in the period 2018-2023. The beaches analyzed were: Prainha, Enseada, Ubatuba, Capri and Itaguaçú located in São Francisco do Sul, north coast of Santa Catarina. The sampling methodology involved the periodic collection of sand samples over a period of one year. The samples were processed by drying, particle size separation and density separation in 5 M sodium chloride saline solution. The larger Mps were manually separated for subsequent plastic characterization by infrared spectroscopy (FTIR). Spectra of virgin polymers were used as comparison standards. The materials separated by density were analyzed and counted by stereoscopic microscopy (10x magnification) and the characterization of smaller particles by optical microscopy, with 40 and 100 x magnification. Multivariate analysis was performed by grouping the samples collected in December (2021), March, June and October 2022, and diagnosed the polymers polypropylene, polyurethane, polystyrene and polyethylene. Most of the particles visualized under the optical microscope were fibers, proving what the authors corroborated about the dominance of fishing carried out on the beaches. In parallel with the experimental work, a systematic literature review was carried out on the topic of microplastics in Brazilian coastal environments, references were found in all countries, but when it comes to work carried out in Brazil, there are still few, therefore there is a need for more studies focused on the topic.